Curatorship or authorship in the creation of scenic biographical documentaries: The cases of Lola Arias and Jérôme Bel (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
What are the boundaries between a creative staging work and a curatorial work? Based on the observation of two series of biographical documentary plays – Mis documentos by Lola Arias (2012-2017) and the Jérôme Bel documentary solos (2004-2009) – we propose a reflection on authorship and curatorship. Even doing similar works, Lola Arias designates her work as "curatorship" while Jérôme Bel does not. This study is interested both in the creative process and in the different paths that led these artists to this form, as well as in the authorial relationships between the stage director and the subject who composes and interprets his biography.
Keywords: Curating; Contemporary dance; Conceptual theatre; Lola Arias; Jérôme Bel